2017
DOI: 10.1016/j.matdes.2017.03.070
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior and failure mechanism of resistance spot welded DP1000 dual phase steel

Abstract: This paper reports on the microstructural evolution of resistance spot welded 1000MPa dual phase steel under two different welding conditions, and their relation to the mechanical performance and failure mechanisms. It is shown that a double pulse weld scheme leads to an enhancement in cross-tension strength compared to single pulse welding. The second pulse subdivides the initial fusion zone of the first pulse into two zones. The inner part is solidified with a columnar structure after the second pulse, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 27 publications
3
39
1
Order By: Relevance
“…The mechanical properties of DP steels depend on martensite volume fraction, martensite islands distribution in the ferrite phase, shape and grain sizes and partitioning of stress-strain between two phases [1,2]. DP steel can be welded using a variety of fusion techniques, including resistance spot [3][4][5][6][7], laser beam [8][9][10][11], plasma arc [12][13][14], friction stir [15][16][17][18] and gas metal arc welding. Xia and Biro investigated the effects of heat input on heat affected zone (HAZ) softening [19], which cannot be avoided in DP steels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of DP steels depend on martensite volume fraction, martensite islands distribution in the ferrite phase, shape and grain sizes and partitioning of stress-strain between two phases [1,2]. DP steel can be welded using a variety of fusion techniques, including resistance spot [3][4][5][6][7], laser beam [8][9][10][11], plasma arc [12][13][14], friction stir [15][16][17][18] and gas metal arc welding. Xia and Biro investigated the effects of heat input on heat affected zone (HAZ) softening [19], which cannot be avoided in DP steels.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al studied laserwelded joints of DP1000 steel, and concluded that they were softened by the tempering and softening of pre-existing martensite and by carbide precipitation [26,27]. Resistance spot-welded DP1000 was studied by Chabok et al, who found that double pulse welding results in a softer HAZ [28]. Tiziani et al evaluated the effects of three types of welding (gas tungsten arc, plasma arc, and electron beam) on the properties of DP600 steel.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance spot-welding (RSW) is the predominant process for joining steel sheet components in the automobile industry. The spot-weld quality is critical to the reliability of the overall automobile as cars typically contain thousands of spot-welds [12][13][14]. Saha et al [15] reported that the TWIP steel was highly susceptible to the liquation crack, and some elements such as C, Mn, and Ti showed strong segregation behavior of TWIP steel after RSW.…”
Section: Introductionmentioning
confidence: 99%
“…The weld zone of the DP 800 joints recorded 584 Hv in the nugget zone, which was higher when compared with the base metal hardness of 295 Hv. The higher hardness in the nugget zone was observed due to formation of columnar/ lath /leaf like martensite phase in the NZ as high cooling rate was observed in the process [12].…”
Section: Hardness Evaluationmentioning
confidence: 94%